Building local partnership through community parks in Central Tokyo: perspectives from different participants - Zong, Min; Xu, Guolin; Yanai, Shigeto (Frontiers in Sustainable Cities, 2024)
Introduction Cities globally, including Tokyo, face challenges in managing small urban green spaces due to limited land, aging infrastructure, and rising maintenance costs. This study explores effective community engagement strategies for park revitalization as cities focus on improving existing green spaces rather than expanding them. Methods This research investigates community park revitalization in Toshima Ward, Tokyo, using a case study approach involving three parks. Data were collected through interviews with seven park management stakeholders and a survey of 176 residents. The study aimed to identify key factors for successful community participation, evaluate perceptions of engagement activities, and assess residents’ willingness to participate. Results Key factors for effective park revitalization include public buildings inside and outside the parks, sufficient greenery and open spaces, and local responsible persons. Despite these conditions, challenges such as high maintenance costs and low resident engagement persist. Among 176 respondents, 55 had participated in park events. Both genders noted increased use by parents and children and enhanced motivation to visit as significant impacts, with mean ratings of 4.36 and 4.37, respectively. Age differences were observed: respondents aged 18-39 emphasized increased use by parents and children (mean 4.75), while those aged 40-59 and over 60 valued motivation to visit (means 4.64 and 4.00). Long-term residents (over 10 years) reported lower impact ratings than newer residents, and larger families rated activities more positively than smaller or single-person households. Key issues included insufficient publicity (60%), restriction of normal use (20%), increased waste (14.5%), and noise (12.7%). Discussion The study highlights the need to address demographic differences in engagement preferences and barriers. Tailoring activities to diverse groups, including seniors and single-person households, can improve participation and effectiveness. These findings can guide localized park management strategies and foster more inclusive urban green space initiatives.